Use of an oxytocin antagonist in in vitro fertilization-embryo transfer for women with repeated implantation failure: A retrospective study - Pei-Yi Chou; Meng-Hsing Wu; Hsien-An Pan; Kuei-Hsiang Hung; Fong-Ming Chang (Elsevier, 2011)
Objective: This retrospective study aimed to investigate the use of an oxytocin antagonist in improving the pregnancy outcome of in vitro fertilization-embryo transfer (IVF-ET) in patients with repeated implantation failure (RIF). Materials and Methods: A total of 150 infertile couples with RIF undergoing IVF-ET were divided into three groups. Patients who did not receive atosiban were used as controls (Group 1; n=80). Forty patients received a single bolus dose (6.75 mg, 0.9 mL/vial) of atosiban before ET (Group 2), and 30 patients received a bolus dose of 6.75 mg atosiban followed by infusion at 18 mg/hr for 3 hours immediately after ET (Group 3). Results: A significantly higher implantation rate (30.21%) was noted in Group 2 compared with Groups 1 and 3 (11.8% and 15.9%, respectively; p=0.0006). The clinical pregnancy rate of Group 2 (37.5%) was significantly higher than that of Groups 1 (12.5%) and 3 (20%) (p=0.0057). The live birth rate was significantly higher in Group 2 (35%) than in Groups 1 and 3 (10% and 16.67%, respectively; p=0.0031). Conclusion: These results suggest that IVF-ET using lower dosage of atosiban may improve pregnancy outcomes of patients with RIF.